Effect of nitrogen source and pH on the growth of a glutamine requiring strain (glm) - R. W. Barratt; W. N. Ogata (Fungal Genetics Reports, 1964)
Effect of nitrogen source and pH on the growth of a glutamine requiring strain (glm)